Evaluating the Concept of Gender Equality in the Islamic Perspective and SDG: An Analysis - Hamisan@Khair, Nur Saadah; Muda, Khadijah; Mohd Ghazali, Norzulaili; Sintang, Suraya (RABBANICA - Journal of Revealed Knowledge, 2021)
In 2015, United Nations (UN) has implemented 17 Sustainable Development Goals (SDGs), where the fifth goal aims to achieve gender equality and empower all women and girls all over the world. The efforts of promoting gender equality are not new, yet it is a continuous mission as a global concern from one generation to another. Islam is one of the religions which attempts to emphasize equality for all mankind. Unfortunately, there are claims that gender inequality and injustice are being justified in the name of Islam. Islamic texts are blamed for having deliberately encouraged gender bias and have shown a preference for males over females. The stereotype image of the female role is continuously portrayed as a symbol of the oppression of Muslim women, even though in the present-day women have been given other significant roles in society. Therefore, this study aims to remove any accusation that claims Islam is an unjust religion towards gender equality and analyse its value within the current context. Applying the qualitative design, this study collects and analyses related verses from the Quran and selected hadiths from six canonical books of hadith known as Kutub Sittah. As a result, the study found the similarity and differences on the concept of gender equality in SDG and the Islamic texts from the Quran and hadith. However, eliminating injustice and discrimination towards women should be significantly continued as a global and humanitarian mission.